Estudo e caracterização térmica da curcumina e de uma forma polimórfica - Fugita, Renan Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This paper was prepared a polymorphic from of curcumin a natural bioactive compound widely used in Indian medicine in the treatment of a range of illnesses. The preparation was the polymorphic crystallization process and solvent mixtures of organic solvents in order to change the dielectric constant of the solution to obtain crystals. The crystal of curcumin has been studied and characterized by absorption spectroscopic in the infrared, X-ray diffraction powder method and by thermo analytical techniques: thermogravimetry and differential therma analysis (TG-DTA) and differential scanning calorimetry (DSC). The DSC of the pure compound (MP=180,19ºC) showed some differences compared the compound crystallized (MP=176.63ºC) in a mixture of solvents thus indicating the phenomenon of polymorphism, and TG-DTA curve of the compound crystallized showed that this was not a solvatomorphic. Finnally the techniques of X-ray diffraction technique FTIR and powder showed a structural change in the compound crystallized, profile-based graphics when compared to the pure compound, which proves that the compound crystallized it is a polymorph

Neste trabalho foi preparada uma forma polimórfica da curcumina, um composto natural bioativo amplamente utilizado na medicina indiana no trato de uma série de enfermidades. A preparação do polimorfo foi mediada pelo processo de cristalização por solventes e misturas de solventes orgânicos a fim de alterar a constante dielétrica da solução para obtenção de cristais. O cristal de curcumina foi estudado e caracterizado por espectroscopia de absorção na região do infravermelho, difratometria de raios X pelo método do pó e pelas técnicas termoanalíticas: termogravimetria e análise térmica diferencial (TG-DTA) e calorimetria diferencial exploratória (DSC). A curva DSC do composto puro (PF= 180,19ºC) mostrou certa diferença quando comparada com a do composto cristalizado (PF=176,63ºC) em mistura de solventes, indicando assim o fenômeno de polimorfismo, e a curva TG-DTA do composto cristalizado mostrou que este não era um solvatomorfo. Por fim as técnicas de difratometria de raios X pela técnica do pó e FTIR evidenciaram uma mudança estrutural no composto cristalizado, baseado no perfil dos gráficos quando comparados aos do composto puro, o que comprova que o composto cristalizado trata-se de um polimorfo
Keywords: Pigmentos (Biologia); Polimorfismo (Cristalografia); Solventes organicos; Espectroscopia de infravermelho; Raios X - Difração; Polymorphism (Crystallography); Pigments (Biology); Organic solvents; Infrared spectroscopy; X-ray diffractometer